Silver Nanoparticles Conjugate Attenuates Highly Active Antiretroviral Therapy-Induced Hippocampal Nissl Substance and Cognitive Deficits in Diabetic Rats - Sodiq Kolawole Lawal; Samuel Oluwaseun Olojede; Ayobami Dare; Oluwaseun Samuel Faborode; Edwin Coleridge S. Naidu; Carmen Olivia Rennie; Onyemaechi Okpara Azu (Journal of Diabetes Research)
Background. The application of nanomedicine to antiretroviral drug delivery holds promise in reducing the comorbidities related to long-term systemic exposure to highly active antiretroviral therapy (HAART). However, the safety of drugs loaded with silver nanoparticles has been debatable. This study is aimed at evaluating the effects of HAART-loaded silver nanoparticles (HAART-AgNPs) on the behavioural assessment, biochemical indices, morphological, and morphometric of the hippocampus in diabetic Sprague-Dawley rats. Methods. Conjugated HAART-AgNPs were characterized using FTIR spectroscopy, UV spectrophotometer, HR-TEM, SEM, and EDX for absorbance peaks, size and morphology, and elemental components. Forty-eight male SD rats (250±13 g) were divided into nondiabetic and diabetic groups. Each group was subdivided into (n=8) A (nondiabetic+vehicle), B (nondiabetic+HAART), C (nondiabetic+HAART-AgNPs), D (diabetic+vehicle), E (diabetic+HAART), and F (diabetic+HAART-AgNPs). Morris water maze, Y-maze test, and weekly blood glucose levels were carried out. Following the last dose of 8-week treatment, the rats were anaesthetized and euthanized. Brain tissues were carefully removed and postfixed for Nissl staining histology. Results. 1.5 M concentration of HAART-AgNPs showed nanoparticle size 20.3 nm with spherical shape. HAART-AgNPs revealed 16.89% of silver and other elemental components of HAART. The diabetic control rats showed a significant increase in blood glucose, reduced spatial learning, positive hippocampal Nissl-stained cells, and a significant decrease in GSH and SOD levels. However, administration of HAART-AgNPs to diabetic rats significantly reduced blood glucose level, improved spatial learning, biochemical indices, and enhanced memory compared to diabetic control. Interestingly, diabetic HAART-AgNP-treated rats showed a significantly improved memory, increased GSH, SOD, and number of positive Nissl-stained neurons compared to diabetic-treated HAART only. Conclusion. Administration of HAART to diabetic rats aggravates the complications of diabetes and promotes neurotoxic effects on the experimental rats, while HAART-loaded silver nanoparticle (HAART-AgNP) alleviates diabetes-induced neurotoxicity.